Supplementation of syringic acid-rich Phrynium pubinerve leaves imparts protection against allergic inflammatory responses by downregulating iNOS, COX-2, and NF-κB expressions. Issue 2 (February 2023) - Islam, Md Arman; Huq Atanu, Md Samiul; Siraj, Md Afjalus; Acharyya, Rabindra Nath; Ahmed, Khondoker Shahin; Dev, Shrabanti; Uddin, Shaikh Jamal; Das, Asish Kumar
Abstract: Background: The present study was designed to characterize the role of ethanolic leaf extract of Phrynium pubinerve Blume (EPP) supplement in attenuating allergic inflammation, encouraged by the presence of syringic acid in it, as this phenolic acid is reportedly promising in suppressing serum immunoglobulin E (IgE) and inflammatory cytokine levels. Materials and methods: HPLC-DAD dereplication analysis was performed to determine the presence of the vital polyphenolic metabolites. The efficacy of EPP against lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 cells was evaluated by measuring its inhibitory effects on NO and ROS/RNS production. The expressions of major inflammation-associated molecules (iNOS, COX-2, NF-κB, IL-6, and TNF-α) in RAW 264.7 cells were assessed through Western blot. Physiological and behavioral changes, BMI, and different biochemical parameters in mice blood serum were investigated in the toxicological assays. Formaldehyde-induced paw edema test in mice was conducted using established animal model. TDI-induced allergic model in mice was carried out to determine different allergy-like symptoms, and differential white blood cell (WBC) counts in blood and bronchoalveolar lavage (BAL) fluid. The intermolecular interaction analysis of the identified major metabolite of EPP with H1R and iNOS was studied by molecular docking. Results: HPLC-DAD analysis showed the presence of syringic acid (89.19 mg/100 g EPP) and a few other compounds. LPS-induced NO generation was reduced by EPP in a concentration-dependent manner, showing IC50 of 28.20 ± 0.27 μg/mL. EPP exhibited a similar inhibitory effect on ROS/RNS production with IC50 of 29.47 ± 2.19 μg/mL. Western blotting revealed that EPP significantly downregulated the expressions of iNOS, COX-2, NF-κB, IL-6, and TNF-α in RAW 264.7 cells when challenged with LPS. The toxicological assays confirmed the dosage and organ-specific safety of EPP. In the formaldehyde-induced paw edema test, EPP caused a 66.41% reduction in mice paw volume at 500 mg/kg dose. It ameliorated TDI-induced allergy-like symptoms and decreased different inflammatory WBCs in mice's blood and BAL fluid in a dose-dependent manner. Finally, syringic acid demonstrated mentionable intermolecular binding affinity towards H1R (−6.6 Kcal/moL) and iNOS (−6.7 Kcal/moL). Conclusions: Collectively, considerable scientific reasoning was obtained in favor of the suppressive potential of EPP against allergic inflammatory responses that are proposed to be exerted via the downregulation of iNOS, COX-2, and NF-κB expressions, H1R antagonism and suppression of cytokines, such as IL-6, and TNF-α.